Prevalence of percutaneous injuries and associated factors among dental surgeons - Ferreira, Fabiana Vargas (2012)
Purpose: The practice of dentistry usually involves contact with secretions from the oral cavity through percutaneous injuries, which is a risk factor for the transmission of infections, especially hepatitis B, between the professional and patients. This study aimed to assess the prevalence of percutaneous injuries and associated factors among dental surgeons. Methods: A total of 187 dental surgeons from the city of Pelotas, Brazil, participated in this study. Data concerning the socio-demographic aspects, occurrence of accidents, types of instruments, use of personal protective equipment, immunization coverage related to hepatitis B and tests for serum conversion were collected through self-reported questionnaires. The data underwent descriptive analysis and chi-square testing or Fisher’s exact test, with P<0.05. Results: The prevalence of percutaneous injuries was 59.8%, and there was no association with the risk factors evaluated. Of the dentists interviewed, 97.3% had been vaccinated against hepatitis B; however, only 86.2% had received the three recommended doses. The use of probes and handling needles were the most common causes of percutaneous injuries (37.0% and 29.0%, respectively). Conclusion: The results showed that the prevalence of percutaneous injuries was high among dental surgeons, and there is a need for emphasis on the prevention of hepatitis B through the administration of the three vaccine doses and the use of personal protective equipment.